Elevated barometric pressure suppresses cell proliferation by delaying the G2/M phase and weakening integrin-mediated cell adhesion and actin assembly - Son, Gwang-ic; Lee, Eunil; Kim, Mari; Lee, Seoeun; Moon, Yesol; Kim, Joonhee (Archives of Biological Sciences, 2023)
Paper description: Evidence suggests that a certain pressure inhibits cell proliferation, however, the mechanism by which pressure reduces cell proliferation has not been fully elucidated. An in-house pressure chamber was designed to produce an environment of 2×atmospheric absolute pressure. The mechanism of cell proliferation induced by elevated barometric pressure (EBP) was studied in H460 cells using RNA sequencing, FACS and multiple assays. Under EBP, cell proliferation was significantly suppressed due to G2/M phase delay, which was intimately connected with weakened cell adhesion and actin assembly. EBP-mediated cell proliferation inhibition can pave the way for treating cancer patients by suppressing cancer progression. Abstract: Human cells are continuously exposed to various stress factors in their physiological environment. Evidence suggests that certain mechanical stress can affect cell cycle progression and cell proliferation. However, the signaling pathways involved in this process are not well understood. To investigate this, we developed a pressure chamber capable of producing an elevated barometric pressure (EBP) environment of 2×atmospheric absolute pressure (ATA). We then studied the effect of EBP on cell proliferation and its underlying mechanism. Our results show that EBP inhibited cell proliferation by delaying the G2/M phase. Specifically, EBP reduced the expression levels of cell adhesion-related genes and downregulated integrin subunit genes, resulting in weaker interaction between cells and extracellular matrix proteins. In addition, Ras-related C3 botulinum toxin substrate 1 (Rac1) and cell division control protein 42 homolog (Cdc42) activity was suppressed, and actin assembly was decreased. These findings suggest that the EBP-mediated G2/M phase delay is due to attenuated cell adhesion and actin cytoskeleton assembly, leading to the inhibition of cell proliferation. Our results provide a crucial molecular mechanism for how certain pressure (changes) can negatively regulate cell proliferation. These findings could potentially be used in the future to develop a pressure therapy to inhibit cell proliferation in cancer patients.